Association Between Hearing Impairment and Self‐Reported Difficulty in Physical Functioning. Issue 5 (29th April 2014) - Chen, David S.; Genther, Dane J.; Betz, Joshua; Lin, Frank R.
<x xml:space="preserve">Abstract</x> Objectives To determine whether hearing impairment, defined by using objective audiometry, is associated with multiple categories of self‐reported physical functioning in a cross‐sectional, nationally representative sample of older adults. Design Multivariate secondary analysis of cross‐sectional data. Setting The 2005–06 and 2009–10 cycles of the National Health and Nutrition Examination Survey. Participants Adults aged 70 and older who completed audiometric testing (N = 1, 669). Measurements Hearing was measured using pure‐tone audiometry. Physical functioning was assessed using a structured interview. Results In a model adjusted for age and demographic and cardiovascular risk factors, greater hearing impairment (per 25 dB hearing level (HL)) was associated with greater odds of physical disability in activities of daily living (odds ratio (OR) = 1.4, 95% confidence interval (CI) = 1.1–1.9), instrumental activities of daily living (OR = 1.6, 95% CI = 1.2–2.2), leisure and social activities (OR = 1.5, 95% CI = 1.1–2.0), lower extremity mobility (OR = 1.4, 95% CI = 1.1–1.7), general physical activities (OR = 1.3, 95% CI = 1.1–1.6), work limitation (OR = 1.4, 95% CI = 1.0–1.9), walking limitation (OR = 1.6, 95% CI = 1.3–2.0), and limitation due to memory or confusion (OR = 1.4, 95% CI = 1.1–1.8). Hearing impairment was not associated with limitations in amount or type of work done (OR = 1.2, 95% CI = 1.0–1.6). Conclusion Hearing impairment in older adults is independently associated with greater disability and limitations in multiple self‐reported categories of physical functioning.